Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan pada Sektor Teknologi - Hesniati Hesniati; Jeslin Jeslin; Candy Candy (Jurnal Bisnis dan Manajemen, 2023)
This research was conducted to see whether there is an influence of Intellectual Capital on the performance of technology companies projected by Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE). This research is quantitative in nature, using secondary data obtained from the annual reports of 15 technology companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The limitation in this study is the lack of samples used because many companies do not meet the criteria. The conclusions based on the research are as follows, Human Capital Efficiency (HCE) has no effect and is not significant on ROA, ROE, and NPM. Structural Capital Efficiency (SCE) has a negative and significant effect on the ROA of the company. However, it is influential and significant to ROE and NPM. Capital Employed Efficiency (CEE) has no effect and is not significant to ROA and NPM. However, influential, and significant to ROE.